The Determinants of On-the-job Search : An Empirical Exploration - Fuentes, Andres (IMF Working Papers; Working Paper, 2002)
There was a surge in the number of employed people looking for another job in the United Kingdom in the 1980s. In this paper, we present a panel analysis of aggregate data and a cross-section analysis of individual data on on-the-job search in the United Kingdom. We find evidence that the availability of jobs and wage dispersion increase on-the-job search. The importance of these results is twofold. First, to the extent that on-the-job search responds to the tightness of the labor market, it can contribute to explaining the observed cyclical behavior of the unemployment outflow rate. Second, as shown in Fuentes (2002), to the extent that changes in on-the-job search can be explained by factors other than labor market tightness, such as wage dispersion, these shift the unemployment-vacancies relationship (the Beveridge curve) and therefore have a role to play in the determination of unemployment.